Altered Functional Connectivity of Striatum Based on the Integrated Connectivity Model in First-Episode Schizophrenia - Zhang, Bei; Lin, Pan; Wang, Xiaosheng; Öngür, Dost; Ji, Xinlei; Situ, Weijun; Yao, Shuqiao; Wang, Xiang (Frontiers in Psychiatry, 2019)
Background: The human striatum is a heterogeneous structure involved in diverse functional domains that related to distinct striatum subregions. Striatal dysfunction was thought to be a fundamental element in schizophrenia. However, the connectivity pattern of striatum solely based on functional or structural characteristics lead to inconsistent findings in healthy adult and also schizophrenia. This study aims to develop an integrated striatal model and reveal the altered functional connectivity pattern of the striatum in schizophrenia. Methods: Two data-driven approaches, task-dependent meta-analytic connectivity modeling (MACM) and task-independent resting-state functional connectivity (RSFC), were used for seven anatomical connectivity-based striatum subregions to provide an integrated striatal model. Then RSFC analyses of seven striatal subregions were applied to 45 first-episode schizophrenia (FES) and 27 healthy controls to examine the difference, based on the integrated model, of functional connectivity pattern of striatal subregions. Results: MACM and RSFC results showed that striatum subregions were associated with discrete cortical regions and involved in distinct cognitive processes. Besides, RSFC results overlapped with MACM findings but showed broader distributions. Importantly, significantly reduced functional connectivity were identified between limbic subregion and thalamus, medial prefrontal cortex, anterior cingulate cortex and insula, and also between executive subregions and thalamus, supplementary motor area and insula in FES. Conclusions: Combing functional and structural connectivity information, this study provides the integrated model of cortico-striatal subcircuits and confirms the abnormal functional connectivity of limbic and executive striatum subregions with different networks and thalamus, supporting the important role of the cortico-striatal-thalamic loop in the pathophysiology of schizophrenia.